The effects of the Fund for the Improvement of University Quality on the National University of Córdoba - María Celeste Escudero (Arizona State University, 2018)
University public financing policy reforms in Argentina during the 1990s were aligned to global and regional developments. Thus, in 1995, the Fund for the Improvement of University Quality (FOMEC) was created, an instrument for allocating additional funding to the historical budget, which prioritized the improvement of teaching over other activities. Based on the theoretical framework of Stephen Ball and the Sociological New Institutionalism, this paper seeks to answer: What effects has the FOMEC had at the National University of Cordoba (UNC), Argentina? This research utilizes hierarchical and discriminant cluster analysis to identify the distribution of FOMEC projects among the participating academic units. Stakeholders' perceptions were analyzed through interviews and documents. Data analysis suggests three core effects. First, FOMEC projects were not distributed in a homogenous way among the academic units within UNC, varying significantly among different disciplinary areas. Second, institutional change conformed to coercive and mimetic forces. Lastly, there are internalization processes of at least five partial innovations in their work cultures, such as: "Strategic Planning of Activities", "Project Management", "Teamwork", "Evaluation Processes" and "Management of Alternative Resources to the Budget".